Evaluation of the Effectiveness of Immunotherapy in Combination with Conventional Treatment Modalities in Early-Stage Breast Cancer (Eurasian Medical Research Periodical, 2025)
Breast cancer remains the most frequently diagnosed malignant disease among women worldwide and continues to represent a major cause of cancer-related morbidity and mortality. Despite significant advances in screening, early detection, and multidisciplinary treatment, breast cancer poses ongoing clinical challenges due to its biological heterogeneity and variable response to therapy. Early-stage breast cancer, generally defined as stages I–II according to the TNM classification, is associated with favorable survival outcomes; however, a proportion of patients still experience disease recurrence, progression, or treatment-related toxicity